Eksistensialisme Profetik dalam Al-Qur’an: Kesunyian, Penolakan, dan Keteguhan Para Nabi - Anshori, Irham Thufani; Bahruddin, Muhammad; Raharjo, Resdianto Permata (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2025)
This research is rooted in the phenomenon of spiritual estrangement experienced by prophets as recorded in the Qur’an, reflecting existential silence within the prophetic process. This silence is not merely physical isolation but a profound inner contemplation in relation to God and society. The objective of this study is to explore the existential dynamics within the Qur'anic prophetic narratives through a religious literary hermeneutic approach. The study employs a descriptive qualitative method with an interpretive-thematic framework, supported by the religious existentialist theories of Kierkegaard, Gabriel Marcel, and Muhammad Iqbal, as well as Mustansir Mir’s Qur’anic narratology. Primary data were drawn from verses containing the inner experiences of prophets, while secondary data came from classical and contemporary exegesis literature. The findings reveal that prophetic narratives contain dramatic structures emphasizing spiritual transformation through suffering, rejection, and isolation elements that strengthen prophetic faith and mission. The conclusion of this study is that the existential silence of prophets is not merely a form of alienation, but a path to the highest spiritual attainment, inspiring ethical resilience and contemplative strength in modern human life.